KESETIAAN NABI YESAYA DAN RELEVANSINYA BAGI PENGABDIAN HAMBA TUHAN MASA KINI - Sostenis Nggebu; Viceta Pomida Agustina (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
The problem studied in this article is to answer the importance of God's servants remaining faithful in serving the work of God entrusted to them. Loyalty in serving God's work is a servant character that is required from God from the start of serving until reaching the finish line. The method used in this article is a literature study method. The result shows that the faithfulness of a servant of God reflects his personal character. He is a man who holds strong commitments before God as shown by the prophet Isaiah. Despite rejection from the leaders and people of Judah, Isaiah remained faithful in prophesying until the end of his life. This model of a servant of God is needed in today's ecclesiastical ministry to serve the congregation so that they remain faithful in their faith even though they are faced with current turmoil and challenges.